(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article discusses the issues of the organization of production in modern conditions, the principles that should be taken into account in it’s improvement, the tasks facing enterprises today, the main directions of modernization of production based on the use of automated control systems. The article also discusses various methods of organizing production in foreign countries, as well as the main problems and ways of solutions in the study area.